2018
DOI: 10.1242/jeb.157131
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction, experience and neural mechanisms underlying mosquito host preference

Abstract: Mosquitoes are best known for their proclivity towards biting humans and transmitting bloodborne pathogens, but there are over 3500 species, including both blood-feeding and non-blood-feeding taxa. The diversity of host preference in mosquitoes is exemplified by the feeding habits of mosquitoes in the genus that feed on ant regurgitation or those from the genus that favor amphibian hosts. Host preference is also by no means static, but is characterized by behavioral plasticity that allows mosquitoes to switch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 145 publications
1
67
0
Order By: Relevance
“…There are over 3500 species of mosquitoes that exhibit remarkable diversity in feeding preferences, from flowers to humans and other mammals, and even frogs or birds 1,2 . Despite their often specific preferences for blood-hosts, mosquitoes exhibit a high degree of behavioral flexibility 3 . One mechanism for this flexibility is their capacity to learn and modify feeding preferences.…”
Section: Introductionmentioning
confidence: 99%
“…There are over 3500 species of mosquitoes that exhibit remarkable diversity in feeding preferences, from flowers to humans and other mammals, and even frogs or birds 1,2 . Despite their often specific preferences for blood-hosts, mosquitoes exhibit a high degree of behavioral flexibility 3 . One mechanism for this flexibility is their capacity to learn and modify feeding preferences.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is often underappreciated when compared with blood-feeding because it is during the latter that transmission of pathogens can occur. A few mosquito genera feed solely from plant sources [3], while in hematophagous (see Glossary) species, females consume sugar sources as well as blood. If deprived of sugar, males typically die within 4 days of eclosion [4].…”
mentioning
confidence: 99%
“…Malaria-transmitting mosquitoes are often described as primary or secondary vectors with this categorisation informed, in part, by their level of anthropophagy as indicated by their HBI. Owing to the influences of different environmental settings, however, studies reporting HBI for the same vector species demonstrate considerable variability 21,[23][24][25] . We recently showed that the HBI of Anopheles coluzzii varied significantly over an extraordinarily small spatial scale, thus demonstrating how localised host biting behaviour can be 26 .…”
mentioning
confidence: 99%